Tumor-associated Tn and STn antigens: from molecular mechanism to precision diagnosis and treatment - Zhao, Shuailong; Fu, Cegang; Gong, Boya; Wu, Hongyan; Zhang, Ruitao; Cai, Huili; Chen, Haidan (Frontiers in Immunology, 2025)
BackgroundAbnormal protein glycosylation is a key feature of tumors. Among the modifications, Tn antigen (GalNAcα1-Ser/Thr) and its sialylated derivative, STn antigen (Neu5Acα2-6GalNAcα1-O-Ser/Thr), are prominent tumor-associated carbohydrate antigens. These antigens exhibit abnormal accumulation in epithelial malignancies, including colorectal cancer, breast cancer, and pancreatic cancer. Their pathological overexpression primarily stems from inactivation of the COSMC/T-synthase axis, either due to genetic mutations or epigenetic silencing, leading to truncated O-glycan biosynthesis.FindingsTn/STn antigens directly promote tumor progression by activating oncogenic signaling pathways (e.g., EGFR/FAK) and inducing epithelial-mesenchymal transition. Additionally, these antigens play a noticeable role in immune suppression in the tumor microenvironment. Tn antigens bind to macrophage galactose-specific lectin (MGL) on myeloid cells, while STn antigens interact with sialic acid-binding immunoglobulin-like lectins (Siglecs), collectively inhibiting natural killer cell cytotoxicity, dendritic cell maturation, and T cell activation. Changes in serum levels of glycoprotein tumor markers (e.g., CA15–3 and CA125) are associated with aberrant protein glycosylation in cancer cells, which may influence their expression levels, stability, or immunodetection. Current therapeutic approaches include monoclonal antibodies (e.g., Remab6, L2A5), antibody-drug conjugates, CAR-T cell therapies, and vaccines. However, challenges remain due to glycan heterogeneity and low immunogenicity.ConclusionTn/STn antigens play a pivotal role in tumorigenesis and immune evasion, presenting significant potential for both diagnostic and therapeutic applications. Future research should concentrate on elucidating the underlying mechanisms, developing innovative detection technologies, and promoting multidisciplinary collaborations to advance Tn/STn antigen-based tumor molecular subtyping, precision targeted therapies, and efficacy prediction systems, thereby providing new directions for cancer diagnosis and treatment.